Strategi Optimasi Pemasaran Air Mineral di Kecamatan Maduran dengan Menggunakan Teori Permainan - Shahadah, Zaqiyatus; Aris Alfan; Zumrotus Sya'diyah (JMT (Jurnal Matematika dan Terapan), 2024)
Mineral water company must design an effective marketing strategy to find optimal marketing opportunities. The method for developing marketing strategies that need to be optimized is using game theory. This research aims to analyze the optimal marketing strategy for mineral water Aqua, Cleo, and local brands (Como, Aidrat, Ake, etc.). Alternative strategies implemented include: profit, demand and quality. In this study, the optimal strategy for Aqua is demand and quality, the optimal strategy for Cleo is profit and demand, and the optimal strategy for Local Brands (Como, Aidrat, Ake, etc.) is profit and demand.